2017
DOI: 10.4172/2161-1041.1000184
|View full text |Cite
|
Sign up to set email alerts
|

Two de novo Overlapping Interstitial Duplications at 10q22 Associated with Speech Impairments, Behaviour Problems, Genital Anomalies, Developmental Delay and Intellectual Disability

Abstract: Copy number variants (CNVs) involving the 10q22 chromosomal region are rarely reported. At present, only eight patients with deletions at this locus have been reported. The reciprocal duplications are rarer and have never been described. Here, we report two unrelated patients with de novo overlapping duplications at 10q22 detected by high-resolution chromosomal microarray analysis (CMA). CMA revealed two duplications: arr 10q22.1q22.3(72331092-78710233) × 3 dn and arr 10q22.1q22.3(70742930-80565963) × 3 dn. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…They have been described in asymptomatic individuals, as well as in patients showing intellectual disability, developmental delay, global growth retardation, epilepsy, seizures, hypotonia, gastroesophageal and vesicoureteral refluxes, constipation, sleep apnea, eczema, and skeletal system anomalies. 8,9,15 The effect in some individuals may change depending on genetic and/or To date, over 30 cases with variable deletions of 10q11.22-q11.23 have been reported in literature. Chen et al reported a 22-week fetus with a 10q11.21q11.23 (45,946,150-50,945,014) Â 1 deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been described in asymptomatic individuals, as well as in patients showing intellectual disability, developmental delay, global growth retardation, epilepsy, seizures, hypotonia, gastroesophageal and vesicoureteral refluxes, constipation, sleep apnea, eczema, and skeletal system anomalies. 8,9,15 The effect in some individuals may change depending on genetic and/or To date, over 30 cases with variable deletions of 10q11.22-q11.23 have been reported in literature. Chen et al reported a 22-week fetus with a 10q11.21q11.23 (45,946,150-50,945,014) Â 1 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…They have been described in asymptomatic individuals, as well as in patients showing intellectual disability, developmental delay, global growth retardation, epilepsy, seizures, hypotonia, gastroesophageal and vesicoureteral refluxes, constipation, sleep apnea, eczema, and skeletal system anomalies. 8 9 15 The effect in some individuals may change depending on genetic and/or nongenetic modifiers. The only clinical feature common to a majority of patients were intellectual disability and developmental delay.…”
Section: Discussionmentioning
confidence: 99%